Peculiarities of Collaboration in Ukraine and West Europe during World War Two: Comparative Analysis of English and German Historiography - Семененко, Валерій; Петровський, Володимир (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
The problem of collaboration in Nazi-occupied Ukraine and Western Europe by Germany and its allies is discusses in this article. It is emphasized that almost 75 years after the end of World War II, discussions on this issue have not stopped yet, which intensified after Western historians proved the futility of the efforts of a number of politicians to present a number of nations as exclusively victims of the invaders. Some examples of such attempts made by Charles de Gaulle in France are cited in the article. Analysis of English- and German-language historiographical sources of the late XX – early XXI centuries testifies that the authors deviate from the «black and white» opposition of the «collaboration-resistance» ligament and prove that there were a lot of «gray zones» in it. We are also talking about those varieties of the occupation regime that inevitably predetermined the scale and forms of collaboration and its impact on the society. The history of the appearance of the interpretation of the «collaboration» concept starting with the XIX century and its political and emotional interpretation during World War II is considered. It is proved that in almost all European countries including Ukraine the number of active collaborators that is individuals who collaborated with the occupiers on an ideological basis remained small. The vast majority of citizens adapted to the situation choosing the model of behavior that corresponded to their moral and ethical qualities. Considerable attention is paid to the analysis of the motives of collaboration, the spectrum of which was very diverse. In addition it is very difficult to establish the true reasons for cooperation with the occupiers because the collaborators understood well the attitude towards them in the society and therefore disguised themselves. The conclusion of the authors of monographs and articles is unequivocal: the occupation regime in Ukraine and in the countries of Western Europe differed significantly in character especially in terms of cruelty and cynicism. It has been established that helpfulness or passive helpfulness was characteristic for most Western Europeans. Neither resistance nor active cooperation with the occupiers was equally undesirable for them. It is noted that the attempts to selectively read the past still do not stop which is unacceptable from the point of view of the true memory of World War II. The conclusion that the collaboration is more beneficial for the occupiers cannot be an excuse for hiding the facts of cooperation with the occupiers of the local population.